2005
DOI: 10.1088/0953-2048/18/3/r02
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear microwave properties of highTcthin films

Abstract: This review presents an overview of the recent developments and achievements in the field of nonlinear microwave physics and applications of high temperature superconducting (HTS) thin films. It touches upon such issues as power-dependent surface impedance Z s , harmonic generation and intermodulation distortion. Various possible sources of the nonlinearity including grain boundaries, patterning, impurity doping, oxygen content and microwave heating are analysed and surveyed. Correlative studies of microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…15. This hysteretic behavior enables an experimental separation of the vortex contribution to R i from reversible mechanisms due to sound generation 78 , dielectric losses in the substrate 79,80 etc. The total surface resistance R s can be written as a sum of the vortex component R i and the BCS resistance…”
Section: B Residual Surface Resistance At B0 ≪ Bvmentioning
confidence: 99%
“…15. This hysteretic behavior enables an experimental separation of the vortex contribution to R i from reversible mechanisms due to sound generation 78 , dielectric losses in the substrate 79,80 etc. The total surface resistance R s can be written as a sum of the vortex component R i and the BCS resistance…”
Section: B Residual Surface Resistance At B0 ≪ Bvmentioning
confidence: 99%
“…Nonlinearities in superconducting films and resonators are widely studied in the context of high-T c superconductors for different applications, 6 with critical temperatures ranging from 9 K ͑niobium͒ to 87 K ͑YBCO͒. Nonlinear behavior is found to originate from thermal instabilities due to local hot spots 7,8 and vortices [9][10][11] leading to a power-dependent surface impedance.…”
Section: Introductionmentioning
confidence: 99%
“…14,19 In most mechanisms, the superconductor film quality plays a crucial role in the power handling. 6 Quasiparticle heating is sometimes mentioned but neglected due to the relatively high thermal conductivity of high-T c superconductors. Where thermal effects play a role, they are caused by local heating due to film inhomogeneities 8,20 or measured by an external resonant probe.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of considerable effort, an universal model able to explain all the observed features has not yet been developed. Reviews of the results on the nonlinear MW surface impedance and the proposed models have been discussed in [5,6,8,28]. A common characteristic is that for H MW < H c1 j , R s varies quadratically with the frequency and the field-induced Z s variations are small and not easily detectable [8,28] [29,30]; others describe the nonlinearity of Z s considering dynamics of Josephson fluxons in grain boundaries [28].…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of the results on the nonlinear MW surface impedance and the proposed models have been discussed in [5,6,8,28]. A common characteristic is that for H MW < H c1 j , R s varies quadratically with the frequency and the field-induced Z s variations are small and not easily detectable [8,28] [29,30]; others describe the nonlinearity of Z s considering dynamics of Josephson fluxons in grain boundaries [28]. It has been suggested that, in order to recognize the process responsible for the field-induced variations of Z s , an useful parameter is r ≡ X s / R s , though in some cases no correlation between R s and X s has been observed [8].…”
Section: Resultsmentioning
confidence: 99%